Keys to face school failure at Fundación Pioneros - Navarro Algás, Javier (Avances en Supervisión Educativa, 2011)
To describe how to face the reality of school failure Pioneers Foundation, an organization framed in the field of social education, divide the exhibition into 4 parts: first, a brief reflection on school failure, second general notes entity, thirdly, their values, and to finish the job description in the labor insertion Center along with brief references to the issue in other areas of the institution.